Are image and quality of tourist services strategic determinants of satisfaction? Millennials' perspective in emerging destinations - Irena Travar; Nikola Todorović; Sanja Pavlović; Eduardo Parra-López (Administrative Sciences, 2022)
This study aims to investigate the level of satisfaction of foreign tourists, specifically millennials, based on different dimensions of destination image and the quality of the tourist services in Belgrade, the capital of the Republic of Serbia, as an emerging destination. Despite the tarnished image attached to the city after the Yugoslav Wars and the economic crisis in the 1990s, this emerging destination is becoming more popular among foreign visitors. A sample of 359 international tourists was surveyed. Structural equation modelling was used to test the relationships between the constructs. The results confirmed the positive effects of image and quality on satisfaction as well as a positive and direct effect of image on quality. Moreover, there was a partial mediation of quality between image and satisfaction. The findings have significant marketing and management implications for destination stakeholders. They provide useful insights for choosing effective strategies and an appropriate business tourism model in emerging destinations that can further help them to become more competitive.
Keywords: 350; Belgrade; destination image; emerging destination; millennials; quality services; Serbia; tourist satisfaction